Elephants know a good thing when they see it - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The Marula tree (Schlerocarya birrea) is known in southern Africa as the elephant tree. When the olive green fruits start to ripen in February, elephants are lured from far away. They start to overeat themselves, drink a lot of water, run around to...